Czynniki skłaniające chińskich studentów do wyboru polskiego szkolnictwa wyższego - Diao, Rui (Studia Edukacyjne, 2020)
Diao Rui, Factors for Chinese Students Choosing Poland Higher Education [Czynniki skłaniające chińskich studentów do wyboru polskiego szkolnictwa wyższego]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 421-434. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.23 As the world’s second largest economy, China has attracted extensive attention from the rest of the world in various aspects. Education, as a way to export talent, has always been valued by the world. Although China’s education industry is growing, many Chinese students still choose to study abroad. China is one of the world’s leading exporters of international students. Poland, located in Europe, has a clean educational environment, advanced European knowledge and unique cultural charm. In recent years, Sino-Polish relations have grown so close that studying in Poland will be a good choice for Chinese students. This article mainly introduces the admission of Chinese elite universities and the study and life of Chinese students in Poland.